Chemical Composition, Antidiabetic, Anti-inflammatory and Antioxidant Activity of Inula ensifolia L. Essential Oil. Issue 4 (4th July 2019) - Sen, Ali; Kurkcuoglu, Mine; Senkardes, Ismail; Bitis, Leyla; Baser, Kemal Husnu Can
Abstract: The essential oil from aerial parts of Inula ensifolia L. obtained by hydro-distillation was analysed by GC and GC/MS and evaluated for antidiabetic activity using α-amylase and α-glucosidase inhibitory methods, anti-inflammatory effect using lipoxygenase inhibitory method as well as antioxidant activity using ABTS method. Fifty seven components were identified, representing 91.7 % of the essential oil. Hexadecanoic acid (12.4 %), 1, 8-cineole (9.1 %), β-bourbonene (4.8 %), intermedeol (4.2 %), muurola-4, 10(14)-dien-1-ol (4.1 %) were the major compounds. The essential oil with IC50 value of 23.66 μg/ml showed strong antilipoxygenase activity. Also, the oil exhibited good α-amylase and mild α-glucosidase inhibitory activity with IC50 values of 45.88 and 262.90 μg/ml, respectively. Essential oil with IC50 value of 102.3 μg/ml displayed good antioxidant activity against ABTS radical. This is first report on chemical composition and biological activity of I. ensifolia essential oil. The results indicated that the essential oil was rich in sesquiterpene compounds and had a remarkable anti-inflammatory activity with good antioxidant and antidiabetic activities.